The effect of irregular stand structures on growth, wood quality and its mitigation in operational harvest planning of Pinus patula stands - Ackerman, Simon Alexander (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScFor)--Stellenbosch University, 2013.